A long‐term shift in the summer distribution of Hector's dolphins is correlated with an increase in cruise ship tourism. Issue 10 (11th September 2022) - Carome, William; Slooten, Elisabeth; Rayment, William; Webster, Trudi; Wickman, Lindsay; Brough, Tom; Dawson, Stephen M.
Abstract: Before the 2020 COVID‐19 pandemic, cruise ship tourism had been one of the fastest growing segments of global tourism, presenting a range of potential impacts. At Akaroa Harbour, Aotearoa New Zealand, the number of annual cruise ship visits more than quadrupled following earthquake damage to Ōtautahi Christchurch's Lyttelton Port in 2011. Akaroa Harbour is an area of core use for endangered and endemic Hector's dolphins ( Cephalorhynchus hectori ). Dolphins here are exposed to some of the highest levels of cetacean tourism in Aotearoa New Zealand. Relationships were examined between growth in cruise ship visits, as well as tours focused specifically on dolphins, and long‐term trends in summer distribution of Hector's dolphins at Akaroa Harbour, from 2000 to 2020. Core use areas for Hector's dolphins within the harbour were quantified via kernel density estimation using data from 2, 335 sightings from over 8, 000 km of standardized survey effort. Data were allocated into four periods based on varying levels of tourism. Dolphin habitat preference varied over time, with the greatest change occurring between 2005–2011 and 2012–2015. When comparing these periods, the spatial overlap of core habitat was less than 24%. Dolphin distribution shifted towards the outer harbour after 2011 and has remained relatively consistent since. The observed shift in distribution coincided with the more than fourfold increase in annual cruise ship visits to Akaroa Harbour. Several pressures related to cruise ship tourism are likely to have influenced habitat preferences of dolphins. Further investigation into causal factors of the observed shift is warranted. In the wake of the COVID‐19 pandemic, the future of cruise ship and wildlife tourism is in flux. Our findings suggest that the future re‐development of this industry should follow a precautionary approach, with the onus on industry to provide evidence of sustainability before proceeding.